Efek Dekontaminasi Karkas Ayam Pedaging Menggunakan Asam Asetat, Asam Sitrat dan Kombinasinya Terhadap Angka Lempeng Total Campylobacter sp. - Zalhendra Eka Putra; Nurliana Nurliana; Razali Razali (Agricultural Faculty, 2014)
(Effect of poultry carcas decontamination by acetic acid, citric acid and its combination to total plate count of Campylobacter sp).ABSTRACT. This research aimed to detect the total number of Campylobacter sp. on poultry carcass after decontamination by acetic acid, citric acid and combination of both. This research was conducted in the Laboratory of Veterinary Public Health Syiah Kuala University, Banda Aceh. The research was factorial completely randomized designed. Samples of poultry carcass were obtained from the Lamnyong market, Banda Aceh. Sixty poultry carcasses were divided into three groups of treatment and one group without treatment. Observation of each treatment was five time replicated at 0, 2, 4, 6 and 8 hours after immersion for 30 seconds in each of the decontamination material. Observation of Campylobacter sp. was done by inoculating every sample on CM0739 selective Campylobacter Blood free selective agar base and CCDA Selective supplement SR0155E. Measurements of Total Plate Count (TPC) Campylobacter sp according to Standard Plate Count (SPC). Data was variance analyzed (ANOVA) using SPSS. The results of research showed that the growing colonies of Campylobacter sp. were indicated by white colony with surrounded by black zone. Immersion of poultry carcass with acetic acid, citric acid and combination of the both and the observation time had no influence (P0,05) to ALT Campylobacter sp. The research was concluded that carcass to Campylobacter sp. The immersion by acetic acid, citric acid and combination of both and the observation time were not reduce Campylobacter sp. in poultry carcass.